Drug Related Problems (DRPs) pada Pasien Mata Rawat Inap: Kajian Potong Lintang Retrospektif selama Dua Tahun - Utaminingsih, Esthi; Oktasari, Solikhah Rosvita; Cholisoh, Zakky (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Drug-related problems (DRPs) in ophthalmic inpatients may compromise the effectiveness and safety of therapy. This study aimed to identify the characteristics of DRPs among inpatients with eye diseases at Hospital X Tangerang during September 2022–August 2024. A retrospective cross-sectional design was applied, involving 178 patients who met the inclusion criteria. DRPs were identified using the Pharmaceutical Care Network Europe (PCNE) classification version 9.1 through review of prescriptions, clinical data, and medication records. Descriptive analysis were used to determine the DRP occurrence. Results showed that most patients were aged 18–60 years (71.9%), female (55.1%), without comorbidities (82.0%), and received an average of 5 medications during hospitalization. Four DRP cases (2.2%) were identified, consisting of one case of treatment effectiveness (P1.2) 25% and three cases of drug safety problems (P2.1) 75%. The main causes were contraindicated drug use despite guideline adherence (C1.2) 50%, inappropriate drug combinations (C1.4) 25%, and patient non-adherence (C7.1) 25%. The low DRP incidence was likely related to the short hospitalization duration and the predominance of topical therapy with minimal systemic exposure. These findings highlight the important role of clinical pharmacists in therapy monitoring to prevent DRPs in ophthalmic inpatients.